Thermodynamic model and high temperature Raman spectra of Na2O-B2O3 glassforming melts - Chromcikova, Maria; Osipov, Armenak A.; Osipova, Leyla M.; Hruska, Branislav; Liska, Marek; Svoboda, Roman (Elsevier Science SA, 2019)
The set of 33 baseline subtracted and thermally corrected Raman spectra of xNa(2)O center dot(1-x)B2O3 (x = 0.10, 0.15, 0.20, 0.25, 0.30, 0.40, and 0.50) glassforming melts measured at temperatures ranging from 501 degrees C to 1145 degrees C was analyzed. The real error estimated by Principal Component Analysis indicated 3-4 independent components. The Multivariate Curve Analysis (MCR) performed for three components resulted in the Raman spectra (so called loadings) and relative abundances (so called scores) of each component. The thermodynamic model of Shakhmatkin and Vedishcheva (SVTDM) was evaluated for each studied melt. Ten following system components were considered: Na2O, B2O3, 3Na(2)O center dot B2O3 (N3B), 2Na(2)O center dot B2O3 (N2B), Na2O center dot B2O3 (NB), Na2O center dot 2B(2)O(3) (NB2), Na2O center dot 3B(2)O(3) (NB3), Na2O center dot 4B(2)O(3) (NB4), Na2O center dot 5B(2)O(3) (NB5), and Na2O center dot 9B(2)O(3) (NB9). The Malfait's spectral decomposition was performed considering the equilibrium molar amounts of the components with highest abundance, i.e. B, NB, and NB4. The obtained partial Raman spectra were compared with the loadings obtained by MCR. The acceptable coincidence was found. The MCR adjusted scores were close to the SVTDM equilibrium molar amounts of system components considered in the Malfait's decomposition. The obtained results validate the correctness of the SVTDM. (C) 2019 Elsevier B.V. All rights reserved.
Termodynamický model a vysokoteplotní Ramanova spektra Na2O-B2O3 sklotvorných tavenin
Keywords: Borate glass melts; Raman spectra; Thermodynamic model; MCR; borátová skla; Ramanova spektra; termodynamický model; MCR